Preparing a Family Communication Plan for Terrorist Attacks - Rose Barnett (EDIS)
Good family communication requires some degree of advanced preparation, basic steps and logical thinking. This section will outline some decisions you will need to make as well as some specific action steps for you to discuss with your family. It will also provide a format for you to use as an outline for your own individualized Family Communication Plan that will be tailor made for your family in case of need. This document is FCS9201, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611: First published: May 2003.